(untitled) (Human Factors in Design, 2023)
This study presents the development of the Anatomia Tátil 3D project based on the principles of Universal Design (UD). The objective is to create three-dimensional representations of human organs for teaching students. Using Blender software, images from the Atlas 3D Anatomy app are used as references for modeling and subsequent 3D printing. The developed pieces have textures representing organ tissues and include legends in Braille and traditional alphabet. The study complies with the principles of UD, ensuring equality, adaptability, safety, and ease of use for all students, promoting an inclusive and enriching educational experience.